Chemical composition of cuticular waxes and pigments and morphology of leaves of Quercus suber trees of different provenance - Simões, Rita (2020)
The chemical composition of cuticular waxes and pigments and the morphological features of cork oak (Quercus suber) leaves were determined for six samples with seeds of di erent geographical origins covering the natural distribution of the species. The leaves of all samples exhibited a hard texture and oval shape with a dark green colour on the hairless adaxial surface, while the abaxial surface was lighter, with numerous stomata and densely covered with trichomes in the form of stellate multicellular hairs. The results suggest an adaptive role of leaf features among samples of di erent provenance and the potential role of such variability in dealing with varying temperatures and rainfall regimes through local adaptation and phenotypic plasticity, as was seen in the trial site, since no significant di erences in leaf traits among the various specimens were found, for example, specific leaf area 55.6–67.8 cm2/g, leaf size 4.6–6.8 cm2 and photosynthetic pigment (total chlorophyll, 31.8–40.4 ug/cm2). The leaves showed a substantial cuticular wax layer (154.3–235.1 ug/cm2) composed predominantly of triterpenes and aliphatic compounds (61–72% and 17–23% of the identified compounds, respectively) that contributed to forming a nearly impermeable membrane that helps the plant cope with drought conditions. These characteristics are related to the species and did not differ among trees of different seed origin. The major identified compound was lupeol, indicating that cork oak leaves may be considered as a potential source of this bioactive compound